Combined treatment using bismuth sulfide nanoparticles loaded with NANOG decoy oligodeoxynucleotides under X-ray radiation for breast cancer cells - Sara Heidari; Mahmoud Gharbavi; Roghayeh Ghorbani; Hamed Rezaeejam; Behrooz Johari (Scientific Reports)
Abstract Our goal in this study was to develop bismuth sulfide nanoparticles (NPs) that were functionalized with chitosan and incorporated with decoy oligodeoxynucleotides (ODNs) specifically targeting the NANOG transcription factor (designated as Bi@Chi-DEC NPs) in triple-negative breast cancer cells. FT-IR, UV–vis, FESEM, EDX, TEM, DLS, release kinetics, and hemolysis assays were done to validate the successful synthesis of Bi@Chi-DEC NPs. The synthesized spherical particles exhibited a size distribution averaging 213.8 nm, with a zeta potential measured at -3.27 mV. The anticancer properties of the synthesized nanoparticles, along with X-ray irradiation (2Gy), were assessed through a series of cellular assays, including MTT, cellular uptake, apoptosis, cell cycle analysis, scratch, and tumorsphere formation assays on MDA-MB-231 breast cancer cells. Treatment with the synthesized nanoparticles and X-irradiation resulted in a significant reduction in cell viability, tumorsphere formation, and cellular migration, while concurrently enhancing the rate of apoptotic cells and inducing cell cycle arrest at the G2/M phase. It can be inferred that Bi@Chi-DEC NPs possess the potential to serve as a therapeutic modality for cancer treatment, particularly when utilized along with radiation therapy. Further, in vivo studies are warranted to substantiate the efficacy of this therapeutic approach.